2001
DOI: 10.1088/0953-8984/13/5/303
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of Fe-Al multilayer thin films for different annealing temperatures

Abstract: The phase formation during thermal annealing of Fe/Al multilayer thin films prepared by electron-beam evaporation, with an overall atomic concentration ratio of Fe:Al = 1:1, has been studied by Rutherford backscattering spectrometry (RBS), x-ray diffraction spectroscopy (XRD), and conversion-electron Mössbauer spectroscopy (CEMS). At the annealing temperature of 473 K some degree of atomic mixing between Fe and Al layers is revealed only by CEMS. At 573 K a large degree of atomic mixing is indicated also by RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
2
39
0
1
Order By: Relevance
“…The Fe-Al system is selected for this purpose since the largely different chemical mixing at the top and the bottom interface has been established by different experimental methods. [2][3][4] The interface mixing in Fe-Al multilayers has been studied intensively by MS, [5][6][7][8][9][10] as well, and due to the outstanding properties of the alloy system for industrial applications, the M€ ossbauer parameters of the different alloy phases and the dependence of the hyperfine fields (HFs) on the number of Al neighbors in the bcc phase are well studied. 8 MD simulations have already been performed for the Fe(001)/Al (Al on top of Fe) and Al(001)/Fe (Fe on top of Al) interfaces, 11,12 and these indeed show an asymmetry of the top and bottom Fe interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe-Al system is selected for this purpose since the largely different chemical mixing at the top and the bottom interface has been established by different experimental methods. [2][3][4] The interface mixing in Fe-Al multilayers has been studied intensively by MS, [5][6][7][8][9][10] as well, and due to the outstanding properties of the alloy system for industrial applications, the M€ ossbauer parameters of the different alloy phases and the dependence of the hyperfine fields (HFs) on the number of Al neighbors in the bcc phase are well studied. 8 MD simulations have already been performed for the Fe(001)/Al (Al on top of Fe) and Al(001)/Fe (Fe on top of Al) interfaces, 11,12 and these indeed show an asymmetry of the top and bottom Fe interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of the as-deposited sample consists of a sextet and a doublet, while that after heat treatment is a singlet alone. The sextet is broadened, and can be considered to be an overlap of close lying sextets each due to Fe with different number of nearest neighbour Al, indicating a certain degree of interatomic mixing at the interfaces between Fe and Al layers [6]. The spectrum was therefore fitted for a distribution of magnetic hyperfine fields (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multilayers with bilayer periods in the range of 3-60 nm have been deposited by electron beam evaporation [2,3,4], RF sputter deposition [1,5], DC sputter deposition [6] and pulsed laser deposition [7]. Aside from the magnetic properties, the main focus has been on the degree of intermetallic compound formation at room temperature and following a post-deposition anneal.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus is that even at room temperature a broad interface forms by reaction between Fe and Al that is of the order of 1-2 nm wide [3,7]. Upon annealing to sufficiently high temperature, the film converts to a solid-state compound [3,4]. The motivation for the study reported in this paper is to discover if the use of ion assisted deposition, which results in the production of denser, smoother layers, can reduce the width of the interface between the Fe and Al layers.…”
Section: Introductionmentioning
confidence: 99%